Telemedicine in Resource-Limited Settings to Optimize Care for Multidrug-Resistant Tuberculosis - G. Khai Lin Huang; Gibson Pawape; Magdalene Taune; Stenard Hiasihri; Pilar Ustero; Daniel P. O'Brien; Daniel P. O'Brien; Philipp du Cros; Steve Graham; Richard Wootton; Richard Wootton; Suman S. Majumdar (Frontiers Media S.A., 2019)
The emergence and spread of multidrug-resistant tuberculosis (MDR-TB) poses a major threat to the global targets for TB control. In recent years, an evolving science and evidence base for MDR-TB has led to much needed changes in international guidelines promoting the use of newer TB drugs and regimens for MDR-TB, however, there remains a significant implementation gap. Due to the complexity of treating MDR-TB, management of cases is often supported by an expert multidisciplinary team, or clinical expert group. This service is often centralized, and may be delivered through a telemedicine platform. We have implemented a Web-based "store-and-forward" telemedicine service to optimize MDR-TB patient care in Daru, a remote and resource limited setting in Papua New Guinea (PNG). From April 2016 to February 2019, 237 cases were discussed using the service. This encompassed diagnostic (presumptive) and treatment cases, and more recently, support to the scale up of preventative therapy for latent TB infection. There were 75 cases in which the use of Bedaquiline was discussed or mentioned, with a high frequency of discussions occurring in the initial period (26 cases in the first 12 months), which has appeared to decrease as clinicians gained familiarity with use of the drug (15 cases in the last 12 months). This service has supported high quality clinical care and fostered collaboration between clinicians and technical experts in a shared learning environment.